2022
DOI: 10.3390/bios12080662
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Factors Cooperatively Actuated Photonic Hydrogel Aptasensors for Facile, Label-Free and Colorimetric Detection of Lysozyme

Abstract: Responsive two-dimensional photonic crystal (2DPC) hydrogels have been widely used as smart sensing materials for constructing various optical sensors to accurately detect different target analytes. Herein, we report photonic hydrogel aptasensors based on aptamer-functionalized 2DPC poly(acrylamide-acrylic acid-N-tert-butyl acrylamide) hydrogels for facile, label-free and colorimetric detection of lysozyme in human serum. The constructed photonic hydrogel aptasensors undergo shrinkage upon exposure to lysozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…这种检测方法简单, 不 需要专门的仪器设备, 激光笔和刻度尺即可完成测试. 智能二维光子晶体水凝胶光信号易于读取, 结构紧凑, 更易于微型化和便携化, 成为传感技术领域的研究热 点 [12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: 引言unclassified
See 1 more Smart Citation
“…这种检测方法简单, 不 需要专门的仪器设备, 激光笔和刻度尺即可完成测试. 智能二维光子晶体水凝胶光信号易于读取, 结构紧凑, 更易于微型化和便携化, 成为传感技术领域的研究热 点 [12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: 引言unclassified
“…近年来, 不同类型的智能二维光子晶体水凝胶已被 报道. 例如, Meng 等、Wu 等以及本课题组分别报道了 适配体功能化的智能二维光子晶体水凝胶, 实现了对病 毒 [12][13] 、半胱氨酸 [14] 、黄曲霉毒素 [15] 、腺苷 [16] 、蛋白 酶 [17][18] 等的检测. Cai 等 [19] 制备了一种无标记的辣根过 氧化物酶/牛血清白蛋白复合二维光子晶体水凝胶, 用 于检测 H 2 O 2 .…”
Section: 引言unclassified
“…The measurement of the Debye ring diameter is facile and can be performed using only a ruler and a laser pointer. The simple fabrication of 2DPC, the easy functionalization of hydrogels, and convenient measurement of Debye ring diameter endow the 2DPCH sensors with wide use in sensing antibiotics, , proteases, , viruses, and metal ions . Presently, it has been reported that 2DPCH has been developed to detect amino acids, , in which aptamers were used as recognition molecules and were copolymerized into the hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 , 36 , 37 , 38 , 39 , 40 ]. Recently, a smartphone-based surface plasmon-coupled emission (SPCE) platform and photonic crystal-coupled emission (PCCE) technology were also employed in biothiol quantification as well as in biosensing studies [ 41 , 42 , 43 , 44 , 45 , 46 ]. Among these materials, functionalized fluorescent quantum dots have attracted much attention due to their size, photostability, and unique optical properties (Stokes shifts, wide absorption and optimizable PL, etc.)…”
Section: Introductionmentioning
confidence: 99%